МАКТАБ ЎҚУВ РЕЖАСИДА ТЕХНОЛОГИЯ ФАНИНИНГ ҚЎЙИЛИШИ ВА УНИНГ ТАРИХИЙ ТАРАҚҚИЁТИ - Пахратдинова, Р.О. (SCIENCE and SOCIETY, 2022)
The article emphasizes the educational and pedagogical significance of introducing technologies into the curricula of general education schools and research work carried out by scientific supervisors and practitioners, as well as a conscious orientation towards choosing a profession in the development of the technological education system.
Keywords: school; student; course; class; technology; science; education; upbringing; stage; skill; qualification; occupation; interest; design; diligence; methodology